2005
DOI: 10.1586/14789450.2.6.949
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress response: a proteomic view

Abstract: The oxidative stress response is characterized by various effects on a range of biological molecules. When examined at the protein level, both expression levels and protein modifications are altered by oxidative stress. While these effects have been studied in the past by classical biochemical methods, the recent onset of proteomics methods have allowed to study the oxidative stress response on a much wider scale. The input of proteomics in the study of oxidative stress response or in the evidence of an oxidat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 60 publications
2
11
0
Order By: Relevance
“…A number of the regulated proteins like superoxide dismutase, heat shock protein, peroxiredoxin and elongation factor-1 alpha found in this study are consistent with a general oxidative stress response [24], [73], [74]. Homologues to superoxide dismutase (SOD) (such as SSO0316), participate in the scavenging of highly reactive oxygen species across all domains [75], [76].…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…A number of the regulated proteins like superoxide dismutase, heat shock protein, peroxiredoxin and elongation factor-1 alpha found in this study are consistent with a general oxidative stress response [24], [73], [74]. Homologues to superoxide dismutase (SOD) (such as SSO0316), participate in the scavenging of highly reactive oxygen species across all domains [75], [76].…”
Section: Resultssupporting
confidence: 77%
“…phosphorylation, sulfation, glycosylation, carbonylation and cysteine oxidation) are important regulators of protein activity. As discussed above with respect to DPSL and rubrerythrin, these modifications can alter the charge of a protein, which will shift the position on a 2D gel [73]. Of the 19 regulated proteins found in this study, 5 were identified in more than one spot; DPSL (SSO2079), superoxide dismutase (SSO0316), peroxiredoxin (SSO2121), rubrerythrin (SSO2642), elongation factor 1-alpha (SSO0216) and thermosome alpha subunit (SSO0862).…”
Section: Resultsmentioning
confidence: 67%
“…However, only a very small increase in mRNA and protein levels has been observed in such conditions, suggesting no direct role of SsPDO in the oxidative stress response [131]. In agreement with these data, a recent transcriptomic, proteomic, and chemical reactivity analysis, performed in oxidative stress conditions, failed to show any up-regulation of SsPDO, unlike other antioxidant enzymes [140][141][142][143]. By contrast, similar studies conducted on P. furiosus showed that PfPDO is one of the most strongly up-regulated proteins in response to cold adaptation from 95 to 72°C [144].…”
Section: Insight Into Pdo Functionssupporting
confidence: 54%
“…Large scale experiments that allow analysis of oxidative modifications on a proteome-wide scale can now be performed. The modifications that are produced in vivo are attractive biomarker targets, possibly facilitating early diagnosis of a number of diseases [57,61,62]. Peroxynitrite is a reactive nitrogen species (RNS) that may be formed from NO by peroxidase activity and can give rise to nitration products.…”
Section: Protein Side-chain Modification: Mimicking In Vivo Oxidationmentioning
confidence: 99%